ANALISA DRUG RELATED PROBLEM (DRPS) PADA PASIEN GAGAL GINJAL KRONIK STADIUM AKHIR YANG MENJALANI HEMODIALISA DI RSUD 45 KUNINGAN - Diputra, Angga Anugra; Sari, Ika Puspita; Nurulita, Nunuk Aries (P3M STIKes Bakti Tunas Husada, 2020)
Chronic kidney disease (CKD) occurs due to progressive decline in kidney function which requires therapy and is expensive. The complexity of treatment with comorbids in CKD patients increases the potential for Drug Related Problems (DRPs). DRPs The emergence of can be triggered by searching for the type and amount of drugs that are consumed by patients to treat various illnesses, such as chronic diseases. The purpose of this study to know characteristics at chronic renal failure patients, see the criteria for DRPs that appeared and the percentage of DRPs occurring in end-stage chronic renal failure patients undergoing hemodialysis at RSUD 45 Kuningan. The study was conducted with a prospective non-experimental descriptive design, namely the researcher analyzed the potential incidence of Drug Related Problems (DRP) in chronic kidney failure patients undergoing hemodialysis at RSUD 45 Kuningan by taking medical record data and interviews with patients. From the results of research that was carried out at the Hemodialysis Installation of RSUD 45 Kuningan for the period December 2019 to February 2020, there were cases of end-stage chronic renal failure who underwent hemodialysis based on inclusion and exclusion criteria, as many as 85 patients with the form of DRPs that appeared in end-stage chronic renal failure patients. who underwent hemodialysis at RSUD 45 Kuningan were Indication without therapy for 5 events (5.9%), Therapy without Indication for 17 events (20%), Inaccurate drugs for patients with 18 events (21.2%), and drug interactions 17 events (20 %)